Garment Waste Recycled Cotton/Polyester Thermal and Acoustic Properties of Air-Laid Nonwovens - S. Sakthivel; Bahiru Melese; Ashenafi Edae; Fasika Abedom; Seblework Mekonnen; Eshetu Solomon (Advances in Materials Science and Engineering)
This research paper reports a study on thermal and sound insulation samples developed from garment waste recycled cotton/polyester fiber (recycled cotton/PET) for construction industry applications. In this research work, the piece of clothing waste recycled cotton and polyester fiber is a potential source of raw material for thermal and sound insulation applications, but its quantities are limited. To overcome the above problems, apparel waste recycled cotton fiber was mixed with recycled/PET fiber in 50/50 proportions in the form of two-layer nonwoven mats with chemical bonding methods. The samples such as cotton (color and white), polyester (color and white), and cotton–polyester blend (color and white) were prepared. All the samples were tested for thermal insulation, acoustic, moisture absorption, and fiber properties as per the ASTM Standard. Also, the behavior of the six recycled cotton/polyester nonwoven samples under high humidity conditions was evaluated. The sound absorption coefficients were measured according to ASTM E 1050 by an impedance tube method; the acoustics absorption coefficients over six frequencies of 125, 250, 500, 1000, 2000, and 4000 Hz were calculated. The result revealed that recycled/PET/cotton garment waste nonwoven mats were absorbing the sound resistance of more than 70% and the recycled nonwoven mats provided the best insulation, acoustic, moisture absorption, and fiber properties. The recycled pieces of clothing waste cotton/polyester nonwoven mats have adequate moisture resistance at high humidity conditions without affecting the insulation and acoustic properties.